Egg Laying Characteristics and Hatching Habitat of Lekang Turtle (Lepidochelys olivacea) in Binasi Beach Turtle Conservation Area, Central Tapanuli North Sumatera Province - Manurung, Vindy Rilani (AQUACOASTMARINE: Journal of Aquatic and Fisheries Sciences, 2023)
Binasi Beach is located in West Sorkam District, Central Tapanuli Regency, North Sumatra Province and borders the Indian Ocean. This beach is one of the beaches where several types of turtles land. Characteristics of the sandy substrate and coastal vegetation such as sea pine which is not too thick and the beach is sloping make turtles often land to lay their eggs. Semi-natural nests are widely used by conservation communities in an effort to protect endangered turtle eggs in natural habitats. This research was carried out from January to February 2022. The purpose of this activity was to determine the characteristics of the nesting habitat and the location of the turtle eggs (Lepidochelys olivacea) hatching as a turtle conservation area effort on the Binasi coast of North Sumatra Province. The method used is a descriptive survey method. Descriptive survey method is a method of collecting data by direct observation. The results showed a beach length of 1.50 m, narrow beach width, gentle beach slope, tidal type of semi-diurnal tide, white fine sand substrate and other parameters classified as normal for turtle nesting sites. The hatching rate of eggs at Station I is 100%, this is the highest value for each station, followed by station II which has the lowest hatching rate of 93.75% with a total average of 96.87%, this concludes that the success rate of hatching semi-natural eggs is very high good).